Multicenter outpatient dinner/overnight reduction of hypoglycemia and increased time of glucose in target with a wearable artificial pancreas using modular model predictive control in adults with type 1 diabetes. Issue 5 (16th February 2015) - Del Favero, S.; Place, J.; Kropff, J.; Messori, M.; Keith‐Hynes, P.; Visentin, R.; Monaro, M.; Galasso, S.; Boscari, F.; Toffanin, C.; Di Palma, F.; Lanzola, G.; et al.
<x xml:space="preserve">Abstract</x> Aims To test in an outpatient setting the safety and efficacy of continuous subcutaneous insulin infusion (CSII) driven by a modular model predictive control (MMPC) algorithm informed by continuous glucose monitoring (CGM) measurement. Methods 13 patients affected by type 1 diabetes participated to a non‐randomized outpatient 42‐h experiment that included two evening meals and overnight periods (in short, dinner & night periods). CSII was patient‐driven during dinner & night period 1 and MMPC‐driven during dinner&night period 2. The study was conducted in hotels, where patients could move around freely. A CGM system (G4 Platinum; Dexcom Inc., San Diego, CA, USA) and insulin pump (AccuChek Combo; Roche Diagnostics, Mannheim, Germany) were connected wirelessly to a smartphone‐based platform (DiAs, Diabetes Assistant; University of Virginia, Charlottesville, VA, USA) during both periods. Results A significantly lower percentage of time spent with glucose levels <3.9 mmol/l was achieved in period 2 compared with period 1: 1.96 ± 4.56% vs 12.76 ± 15.84% (mean ± standard deviation, p < 0.01), together with a greater percentage of time spent in the 3.9–10 mmol/l target range: 83.56 ± 14.02% vs 62.43 ± 29.03% (p = 0.04). In addition, restricting the analysis to the overnight phases, a lower percentage of time spent with glucose levels <3.9 mmol/l (1.92 ± 4.89% vs 12.7 ± 19.75%; p = 0.03) was combined with a greater percentage of time spent in 3.9–10 mmol/l target range in period 2 compared with period 1 (92.16 ± 8.03% vs 63.97 ± 2.73%; p = 0.01). Average glucose levels were similar during both periods. Conclusions The results suggest that MMPC managed by a wearable system is safe and effective during evening meal and overnight. Its sustained use during this period is currently being tested in an ongoing randomized 2‐month study.